User Acceptance of Crash Helmet by Motorcyclists in Malaysia: An Empirical Analysis - Yusuf, Muhammad-Bashir Owolabi; Oluwatoyin, Onikosi-Alliyu Saidat (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
Malaysia ranks among the first twenty countries with the highest death rate from road accidents with death from motorcycle accidents accounting for more than sixty percent of this death rate. The Malaysian government, in the year 2010, started the enforcement of helmet (head protector) in an effort to reduce the rate of death from this source. This paper examines users‟ acceptance of helmet by motorcyclist, using the theory of reasoned action (TRA). The data for this study comes from field survey of motorcyclists in Malaysia. This data was analysed using structural equation modelling. It was discovered that different factors from the theory account for user acceptance of this novelty. The paper concludes by specifying the policy implications of this and recommends other ways of improvement.